Physical activity, exercise habits, and body mass index of adults - Ratna Candra Dewi; Bambang Wirjatmadi (PAGEPress Publications, 2023)
Introduction: The risk of degenerative diseases begins to appear in adulthood. Physical activity and exercise habits prevent the incidence of obesity which is a risk factor for degenerative diseases' emergence. Therefore, this study aims toexamine the relationship between physical activity, exercise habits, body mass index, and fat mass percentage. Design and  Methods: This study used an analytic observational cross-sectional design and 32 office workers in Surabaya aged 28-56 years were selected by simple random sampling technique. The data collected included measurements of physical activity, exercise habits, anthropometry, and body composition, which were analyzed using Spearman's rank correlation test. Results: The results showed that 46.9% of participants had moderate activity, 43.8% exercised 1-2x a week, 56.3% exercised for 20-60 minutes, 56.30% had a low exercise intensity, 62.50% had an overweight body mass index, and 71.9% had overfat mass percentage. Spearman's rank test showed a significant relationship between energy intake, physical activity, exercise frequency, duration and intensity, and body mass index as well as between energy intake, physical activity, exercise intensity, and body fat percentage. Conclusions: Increased physical activity and exercise habits were associated with decreased BMI and body fat percentage.